Psychological Profiles And Performance Variation Among National And State-Level Male Badminton Players: A Comparative Study (International Journal of Food and Nutritional Sciences, 2022)
This study explores the psychological dimensions of badminton players within the context of physical education, focusing on the comparison between national and state-level male competitors. The research aims to profile the psychological characteristics of these athletes, specifically examining anxiety and mindful attention awareness. Rigorous statistical analyses were conducted to ensure the reliability of the results. Initially, the Shapiro-Wilk test was used to confirm the normality of the data, allowing for parametric testing. With normal distribution verified for all variables, descriptive statistics were employed to summarize the mean and standard deviation of the data. Inferential statistics, including an independent t-test, were then used to assess significant differences between the two groups of players. The findings revealed significant differences in anxiety and mindful attention awareness between national and state-level badminton players, indicating variations in their psychological experiences. Consequently, the null hypothesis was rejected at the 0.05 level of significance. These results enhance the understanding of psychological factors in sports and offer practical insights for coaches, trainers, and sports psychologists working with badminton players.